MENINGKATKAN DAYA SAING ENTREPRENEUR INDONESIA MEMASUKI ASEAN – CHINA FREE TRADE AREA - Benardi K., Jemmi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2010)
ABSTRACT Real entrepreneur do not know hard word, existing only successfulness and opportunity, difficulty always there is and surely there is also result of from tiring promising. By growing the spirit of entrepreneur, so we owning is resilient, hard work, and creativity in trying. Minimize useful both for ourselves and or to this nation and others. One clear matter that something each aspect and side surely has risk and surely also promise gold opportunity, that's life which is full of change. A sure entrepreneur has and will deal with resistance. Micro effort nomination in economics more and more to mount along with free trade threat which must be faced at the moment designate economic strength of micro effort have to intensively. On that account needing better arrangement at micro credit market so that is peaceful, efficient, competitive, and also can serve the more micro effort, both for old and new. Keywords: Entrepreneur, CAFTA, competitiveness